Repositioning Proton Pump Inhibitors: Expanding Applications from Acid Suppression to Cancer Therapeutics - Alves, Erica; Bannimath, Gurupadayya; Prabhakaran, Prabitha (Clinical Cancer Drugs, 2025)
Proton pump inhibitors (PPIs), commonly utilized for the management of acid-related disorders, are gaining attention for their repurposing potential in oncology, particularly due to their ability to modulate the acidic tumor microenvironment and disrupt proton transport mechanisms. Beyond their primary role in gastric acid suppression, PPIs exhibit a spectrum of anticancer activities, including inhibition of vacuolar-type H+-ATPase (V-ATPase), disruption of proton gradients, and interference with tumor metabolic adaptation. These effects contribute to increased lysosomal and endosomal pH, impairing autophagic flux, inducing apoptosis, and reducing cancer cell proliferation. Preclinical evidence suggests that PPIs can augment the effectiveness of conventional cancer treatments, such as chemotherapy and immunotherapy, through mechanisms like intracellular modulation of the acidic tumour microenvironment, inhibition of acidic vesicle sequestration, and suppression of efflux transporters (e.g., P-glycoprotein [P-gp], MRP1, BCRP). Furthermore, PPIs offer a promising strategy to counteract drug resistance, a significant challenge in cancer therapeutics. By targeting metabolic reprogramming pathways such as fatty acid synthase (FASN) and TOPK signaling, PPIs impair tumor survival mechanisms, enhance chemotherapy sensitivity, and restore drug efficacy in resistant cancer types. Although the precise molecular pathways responsible for these anticancer effects remain under investigation, the repurposing of PPIs as adjuncts in oncological regimens holds considerable promise. Emerging strategies, including artificial intelligence (AI)-driven drug repurposing, multi-omics biomarker identification, and nanomedicine-based PPI delivery, are expected to optimize their clinical applications. Ongoing and future studies should aim to unravel these molecular mechanisms in greater detail and prioritize clinical trials to evaluate their therapeutic efficacy. This repurposing approach could facilitate the development of innovative strategies to optimize cancer treatment and improve patient outcomes.
Keywords: efflux transporters